Fixes: Of the Forward Discount Puzzle - Flood, Robert P.; Rose, Andrew K. (The Review of Economics and Statistics, 1996)
Regressions of ex post changes in floating exchange rates on appropriate interest differentials typically imply that the high-interest rate currency tends to appreciate, the "forward discount puzzle."Using data from the European Monetary System, we find that a large part of the forward discount puzzle vanishes for regimes of fixed exchange rates.That is, deviations from uncovered interest parity appear to vary in a way which is dependent upon the exchange rate regime.By using the many EMS realignments, we are also able to quantify the "peso problem.